Randomised controlled trial of topical kanuka honey for the treatment of rosacea. Issue 6 (24th June 2015) - Braithwaite, Irene; Hunt, Anna; Riley, Judith; Fingleton, James; Kocks, Janwillem; Corin, Andrew; Helm, Colin; Sheahan, Davitt; Tofield, Christopher; Montgomery, Barney; Holliday, Mark; Weatherall, Mark; et al.
Abstract : Objective: To investigate the efficacy of topical 90% medical-grade kanuka honey and 10% glycerine (Honevo) as a treatment for rosacea. Design: Randomised controlled trial with blinded assessment of primary outcome variable. Setting: Outpatient primary healthcare population from 5 New Zealand sites. Participants: 138 adults aged ≥16, with a diagnosis of rosacea, and a baseline blinded Investigator Global Assessment of Rosacea Severity Score (IGA-RSS) of ≥2. 69 participants were randomised to each treatment arm. 1 participant was excluded from the Honevo group, and 7 and 15 participants withdrew from the Honevo and control groups, respectively. Interventions: Participants were randomly allocated 1:1 to Honevo or control cream (Cetomacrogol), applied twice daily for 8 weeks. Main outcome measures: The primary outcome measure was the proportion of participants who had a ≥2 improvement in the 7-point IGA-RSS at week 8 compared to baseline. Secondary outcomes included change in IGA-RSS and subject-rated visual analogue score of change in severity (VAS-CS) on a 100 mm scale (0 mm 'much worse', 100 mm 'much improved') at weeks 2 and 8. Results: 24/68 (34.3%) in the Honevo group and 12/69 (17.4%) in the control group had a ≥2 improvement in IGA-RSS at week 8 compared to baseline (relative risk 2.03; 95% CI 1.11 to 3.72, p=0.020). The change in IGA-RSS for Honevo compared to control at week 2 minus baseline was −1 (Hodges-Lehman estimate, 95% CI −1 to 0, p=0.03), and at week 8 minus baseline was −1 (Hodges-Lehman estimate, 95% CI −1 to 0, p=0.005). The VAS-CS at week 2 was 9.1 (95% CI 3.5 to 14.7), p=0.002, and at week 8 was 12.3 (95% CI 5.7 to 18.9)¸ p<0.001 for Honevo compared to control. Conclusions: Honevo is an effective treatment for rosacea. Trial registration number: This trial was registered in the Australian and New Zealand Clinical Trials Registry ACTRN12614000004662.